Eres tu mi mama? - Eastman, P. D. (Philip D.). (New York : Beginner Books, una division de Random House, 2016)
"A baby bird falls from its nest and goes in search of his mother"--
"First published in English as Are You My Mother? by Random House Children's Books in 1960"--Copyright page.
Keywords: Birds -- Juvenile fiction; Mothers -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Aves -- Novela juvenil; Madres -- Novela juvenil; Animales -- Infancia -- Novela juvenil; Spanish Juvenile Beginning Readers